Japanese managers’ experiences of neuro-linguistic programming: a qualitative investigation - Kotera, Yasuhiro; Van Gordon, William (The journal of mental health training, education, and practice, 2019)
Purpose Though several work-related mental health training initiatives have been implemented in Japan, the effectiveness of such approaches remains unclear. Consequently, some Japanese corporations prefer using interventions such as neuro-linguistic programming (NLP) to improve employee mental health and wellbeing. This language-based development methodology has been the subject of debate in terms of the quality of the underlying empirical evidence. However, a perspective missing from this debate is an evidence-based understanding of the first-hand experiences of employees that have undertaken NLP training. The purpose of this paper is to inform this debate by conducting a rigorous qualitative examination of the experiences of Japanese senior managers who had recently received training in NLP. Design/methodology/approach Semi-structured interviews attended by 11 Japanese NLP master practitioners were analysed using thematic analysis. Findings Four themes emerged from the data set: improving work-related mental health, NLP fosters a better understanding of the mind, NLP helps to reframe perspectives relating to work and mental health, and challenges of NLP training. Originality/value While managers found NLP training skills such as reframing and neuro-logical levels useful to their managerial practice and mental health more generally, they raised concerns about NLP’s reputation as well as the utility of some of the techniques employed in NLP.